COMPOSITION FOR DYEING KERATIN FIBERS - TSUZUKI, Saki; OZAWA, Rimiko (2017)
The present invention relates to a composition, preferably in the form of an O/W emulsion, for dyeing keratin fibers, preferably hair, comprising: (a) at least one direct dye; (b) at least one fatty material; (c) at least one surfactant; (d) at least one monovalent alcohol other than the (b) fatty material; (e) at least one specific diester compound; and (f) water. The composition according to the present invention can prevent or reduce skin staining by the direct dye on the skin such as the scalp, while providing the keratin fibers with good cosmetic effects such as good coloring properties. La présente invention concerne une composition, de préférence sous la forme d'une émulsion huile-dans-l'eau, pour colorer des fibres de kératine, de préférence les cheveux, comprenant : (a) au moins un colorant direct ; (b) au moins une matière grasse ; (c) au moins un tensioactif ; (d) au moins un alcool monovalent autre que (b) la matière grasse ; (e) au moins un composé de diester spécifique ; et (f) de l'eau. La composition selon la présente invention peut prévenir ou réduire une coloration cutanée par le colorant direct sur la peau, tel que le cuir chevelu, tout en fournissant, aux fibres de kératine, de bons effets cosmétiques, telles que des bonnes propriétés de coloration.